An easy and reliable method to close Petersen's defect using barbed suture to prevent internal hernia from developing after gastrectomy with Roux‐en‐Y reconstruction. Issue 2 (12th July 2019) - Hara, Kentaro; Hayashi, Tsutomu; Nakazono, Masato; Nagasawa, Shinsuke; Shimoda, Yota; Kumazu, Yuta; Yamada, Takanobu; Yamamoto, Naoto; Shiozawa, Manabu; Morinaga, Soichiro; Yoshikawa, Takaki; Rino, Yasushi; et al.
Abstract: Introduction: We propose a novel technique to close Petersen's defect using barbed sutures and evaluate the safety and usefulness of this technique by assessing postoperative complications and measuring the time required to close Petersen's defect. Materials and Surgical Technique: Petersen's defect was closed laparoscopically with running non‐absorbable barbed sutures (V‐loc®) after a nodal dissection and reconstruction procedure. First, the transverse colon was elevated cranially, making the dorsal side of the transverse mesocolon a flattened surface. The intersection of the transverse mesocolon and Roux limb mesentery was then identified, and closure was started from this point. We continued to sew the transverse mesocolon and Roux limb mesentery toward the transverse colon with a running suture. At the end of suturing, we placed one or two stitches in the fatty appendices of the transverse colon and cut the free tail of thread as short as possible. Discussion: We investigated postoperative complications and measured the time required to close Petersen's defect in 64 patients who underwent this technique. The results showed that this closure technique could be performed promptly and safely regardless of the patient, surgical procedure, and the experience of the operator.